Assessment of A Nanoemulsion Gel Made from Moringa Seed Oil using Anticollegenase - Divya Rajput; Saurabh Srivastava (American Journal of Biology and Natural Sciences, 2025)
<span lang="EN-US" style="font-size: 12.0pt; font-family: ’Palatino Linotype’,serif; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-font-kerning: 0pt; mso-ligatures: none; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This study’s goal was to create and assess a moringa seed oil (MSO) nanoemulsion gel utilizing the high-energy emulsification technique. Techniques: By comparing the concentrations of surfactant (tween 80) and cosurfactant (sorbitol) with variations in the concentration of moringa seed oil, a nanoemulsion gel was created utilizing the high-energy emulsification method. Centrifugation testing, viscosity, pH, organoleptic observation (odor, color, clarity, and phase separation), and particle size measurement throughout a 12-week storage period at room temperature are all used to assess the stability of the nanoemulsion gel formulation.